DON'T THROW: A Sustainable Waste Management and Recycling Ecosystem using Digital Innovation - Mahesh Muthu B; Ashok Kumar C
The "DON'T THROW" research is an innovative solution addressing inefficiencies in waste management and recycling. Designed as a dual-app system for users and scrap dealers, it integrates digital tools to streamline scrap collection, reduce environmental impact, and promote resource optimization. Users can schedule scrap pickups at their convenience, with their orders routed to nearby professional dealers. Dealers benefit from a steady income by leveraging the app's network. Additionally, small and medium-sized enterprises are integrated into the system for scheduled scrap collection, ensuring a steady revenue model for the company. Future enhancements include an e- commerce platform, enabling users to exchange scrap for goods, thus fostering a circular economy. This paper explores the architecture, modules, and potential applications of "DON'T THROW" in transforming the waste management industry.